Meta-startup: uma metodologia para o desenvolvimento de startups - FERREIRA, Paulo Weskley de Almeida (2020)
With the advent of mobile computing, it has created a myriad of possibilities for innovation in business. This breakthrough has allowed new entrepreneurs to create businesses with smaller amounts of initial investment and to some extent democratized the market. The consequent intensification of the creation of new companies has generated an increase in the possibilities of innovation occurrence. However, undertaking in Brazil is not an easy task because of problems generated by high bureaucracy, tax burden and scarcity of skilled and specialized manpower, and in most cases, lack of experience or guidance when starting a venture. These factors end up affecting the quality in the production of a good or provision of the service offered. This work presents a methodology focused on the creation of startups in an initially regional context. It is the aggregation of Consultancy, Development and Marketing techniques applied in a work environment of a startup in the city of Belém do Pará. The proposal also presents the tool called Ulha, which allows clients to follow up on all the progress of the project through the web interface. All the support needed to support the proposal was described, as well as the citation of some ventures that collaborated to inspire this model. The result of this proposal is to present data about the usability of the Ulha tool.